Evaluation of STEM Integration in Science Teaching Materials: An Independent Curriculum Perspective - Dody Hermanto; Didit Ardianto; Anna Permanasari (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to evaluate the level of integration of STEM components in the science teaching materials of the Independent Curriculum. The focus of the evaluation includes the dimension of integration between STEM disciplines as well as the relevance of the learning context to real-world problem solving. Methodology: The research uses a qualitative descriptive method, analyzing 31 science learning modules using the Bybee STEM evaluation model. Data were collected through document analysis with a focus on the variables of coordination, combination, and linkage of STEM disciplines. Main Findings: The results show that science is dominant as the main context (100%) with the integration rate of technology and mathematics at 77% and 61%. However, the engineering aspect is only integrated by 23%, indicating a lack of attention to engineering design. Novelty/Originality of this study: This research provides new insights into the challenges of STEM implementation in Indonesia, especially in the context of developing balanced and comprehensive science teaching materials.